Nitrogen in the production of green and dry mass and the efficiency of nitrogen conversion and apparent recovery of pearl millet cultivars - Buso, Wilian Henrique Diniz (2015)
The potential of dry (DM) and green (GM) matter yield, plant nitrogen concentration (NC), apparent nitrogen conversion efficiency (NCE) and apparent N recovery (ANR) of pearl millet cultivars with nitrogen fertilization are analyzed. Current experiment was conducted in the municipality of Ceres GO Brazil, within the Cerrado (Brazilian savannah) biome. A 3x4x2 randomized factorial block design was employed, with three repetitions. Treatments were composed of three pearl millet cultivars (ADR-7010, ADR-500 and BRS-1501), four N doses (0, 50, 100 and 200 kgha-1) and two sowing times (December and February). Plants from each seeding were harvested twice at a height of 0.70 m. There was a significant effect on the interaction between cultivars and N doses. GM yield of ADR-7010 cultivar increased up to 140 kg.ha-1 of N. There was a quadratic effect of N doses on DM yield, with maximum production at 158 kg ha-1 N. The quantity of N extracted by the plants varied according to the cultivar, with BRS-1501 accumulating the highest N quantities in the shoots. Maximum NC of pearl millet shoots would be achieved with 147 kg N ha-1. The highest NCE occurred with N doses of 50 kg ha-1, with a DM yield of 11.60 kg per kg of applied N. ANR was also highest for N doses of 50 kg ha-1, with a 53% maximum recovery.